2020
DOI: 10.3390/su12093648
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Game for Collaborative Innovation of the IoT Industry under Government Leadership in China: An IoT Infrastructure Perspective

Abstract: Since the United States, the European Union, China, and other countries put forward the development strategy of Internet of Things (IoT), it has been growing rapidly, leading to industrial restructuring and the sustainable development of various industries. Not only can collaborative innovation of the IoT industry accelerate R&D efficiency and product substitution frequency of IoT infrastructure, but also it can promote the construction of smart cities, the application of Big Data and Cloud Computing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Subsequently, they verified game models and theoretical results based on numerical examples, case studies, and empirical analysis, respectively. Wan and Qie [40] and Hou and Li [41] investigated the tripartite game between the government smart financial poverty alleviation ecosystem and the collaborative innovation system of IoT. As impacted by the different research perspectives and points of departure, the existing studies failed to consider the optimization effect of emerging technologies (e.g., artificial intelligence, big data, cloud computing, and blockchain) on smart platform systems, as well as the interactive decision-making behaviour and evolutionary stable state of intelligent platform system participants under the novel technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, they verified game models and theoretical results based on numerical examples, case studies, and empirical analysis, respectively. Wan and Qie [40] and Hou and Li [41] investigated the tripartite game between the government smart financial poverty alleviation ecosystem and the collaborative innovation system of IoT. As impacted by the different research perspectives and points of departure, the existing studies failed to consider the optimization effect of emerging technologies (e.g., artificial intelligence, big data, cloud computing, and blockchain) on smart platform systems, as well as the interactive decision-making behaviour and evolutionary stable state of intelligent platform system participants under the novel technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hou and Li believed that the government was an advocate of IoT infrastructure construction in China. They established an evolutionary game model that included the government, manufacturers, and operators, and the results showed that each factor had a different impact on them [49]. Li et al built a game model that included enterprises, academic institutions, and governments to explore the impact of government subsidies on innovation [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned in some studies [11][12][13], comprehensive open 5G competition will cause market volatility. Advertising companies have the opportunity to collect some detailed audience information through the deployment of private networks [12], and telecom companies also have the opportunity to profit from various public or private network deployment services [13].…”
Section: Introductionmentioning
confidence: 99%
“…Advertising companies have the opportunity to collect some detailed audience information through the deployment of private networks [12], and telecom companies also have the opportunity to profit from various public or private network deployment services [13]. Of course, if the commercial market changes too much, it may also attract the government's attention and compel legislation to restrict such market competition [11].…”
Section: Introductionmentioning
confidence: 99%